Impacts on terrestrial biodiversity of moving from a 2°C to a 1.5°C target. (2nd April 2018) - Smith, Pete; Price, Jeff; Molotoks, Amy; Warren, Rachel; Malhi, Yadvinder
Abstract : We applied a recently developed tool to examine the reduction in climate risk to biodiversity in moving from a 2°C to a 1.5°C target. We then reviewed the recent literature examining the impact of (a) land-based mitigation options and (b) land-based greenhouse gas removal options on biodiversity. We show that holding warming to 1.5°C versus 2°C can significantly reduce the number of species facing a potential loss of 50% of their climatic range. Further, there would be an increase of 5.5–14% of the globe that could potentially act as climatic refugia for plants and animals, an area equivalent to the current global protected area network. Efforts to meet the 1.5°C target through mitigation could largely be consistent with biodiversity protection/enhancement. For impacts of land-based greenhouse gas removal technologies on biodiversity, some (e.g. soil carbon sequestration) could be neutral or positive, others (e.g. bioenergy with carbon capture and storage) are likely to lead to conflicts, while still others (e.g. afforestation/reforestation) are context-specific, when applied at scales necessary for meaningful greenhouse gas removal. Additional effort to meet the 1.5°C target presents some risks, particularly if inappropriately managed, but it also presents opportunities. This article is part of the theme issue 'The Paris Agreement: understanding the physical and social challenges for a warming world of 1.5°C above pre-industrial levels'.